PENGARUH PERENCANAAN PAJAK, PROFITABILITAS DAN ASET PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA SEKTOR TRANSPORTATION & LOGISTIC YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024) - Feni Andriani; Sri Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Earnings management can be described as a condition in which management implements certain policies in the process of preparing financial statements for external parties so as to reduce profits and increase profits in line with management expectations. Earnings management occurs as a result of a conflict of interest between agents and principals, where managers are driven to meet work targets and compensation, while owners want stable financial statements in order to make investment decisions. This results in unreliable financial statements, as the information contained therein does not reflect the actual situation. The purpose of this study is to analyze the effect of tax planning, profitability, and deferred tax assets on earnings management. The population of this study is all companies in the Transportation & Logistics sector listed on the Indonesia Stock Exchange for the period 2022-2024. The data source used is secondary data in the form of annual financial reports of companies in the Transportation & Logistics sector for three years, namely the 2022-2024 period. This type of research is causality research with a quantitative approach. The technique used in sampling is purposive sampling, with a total of 60 observation data obtained. The data analysis technique used classical assumption tests, namely normality tests, heteroscedasticity tests, autocorrelation tests, and multicollinearity tests. Hypothesis testing used multiple linear regression. The results showed that tax planning and profitability had a negative effect on earnings management. Meanwhile, deferred tax assets had no effect on earnings management. This study is expected to provide practical benefits for transportation and logistics companies in designing more effective financial strategies. From a theoretical perspective, the results of this study support Agency Theory. In an agency relationship, managers have more information than company owners (information asymmetry), which can trigger managers to act opportunistically in managing profits by considering tax planning policies and the company's profitability level.